171 Growth performance of weaned pigs fed a high-protein corn co-product. (7th December 2018) - Martindale, A; Trenhaile-Grannemann, M; Barnett, S; Miller, P; Burkey, T
Abstract: Next-generation protein ingredients derived from dry-mill ethanol production processes are becoming available. NexPro™ (Flint Hills Resources; Wichita, KS) is a high protein corn co-product (HPCP; 50% crude protein) that has emerged from new technologies. The objective of this work was to determine effects of HPCP (NexPro™) on growth performance of weaned pigs. Crossbred barrows (n = 80; initial BW = 6.5 ± 0.51 kg) were weaned at 21 d post-farrowing and assigned to 16 pens and pens were randomly allotted to treatments: 1) control diet (CTL); 2) CTL diet containing 8% HPCP; 3) CTL diet containing 16% HPCP; and 4) CTL diet containing 24% HPCP. Each treatment was replicated 4 times (pens) and each pen contained 5 pigs. Pigs were given ad libitum access to feed and water in an environmentally-controlled room. There were 3 dietary phases (Phase 1: d 0 to 14; Phase 2: d 14 to 28; Phase 3: d 28 to 35) and dietary treatments were maintained in Phase 1 and 2 with a common diet fed in Phase 3. From d 0 to 35, feed disappearance and individual BW were measured weekly for determination of ADG, ADFI, and G:F. During Phase 1, no effects of dietary treatment were observed on growth performance. During Phase 2, ADG (598, 563.7, and 528.4 g, respectively) and ADFI (815.1, 748.3, and 709.5 g) was similar between CTL, 8% HPCP and 16% HPCP; however, ADG and ADFI decreased ( P < 0.02) in 24% HPCP (460.1 and 659.7 g; respectively for ADG and ADFI) compared to CTL. During Phase 3 and overall (d 0 to 35), no effects of dietary treatment were observed on growth performance. Inclusion of HPCP up to 16% does not negatively affect growth performance and may be a cost-effective protein ingredient.